2004
DOI: 10.1172/jci19655
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells utilize CD1a and langerin to efficiently present nonpeptide antigens to T cells

Abstract: Langerhans cells (LCs) constitute a subset of DCs that initiate immune responses in skin.Using leprosy as a model, we investigated whether expression of CD1a and langerin, an LC-specific C-type lectin, imparts a specific functional role to LCs. LC-like DCs and freshly isolated epidermal LCs presented nonpeptide antigens of Mycobacterium leprae to T cell clones derived from a leprosy patient in a CD1a-restricted and langerin-dependent manner. LC-like DCs were more efficient at CD1a-restricted antigen presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 43 publications
(21 reference statements)
2
100
0
1
Order By: Relevance
“…Moreover, Langerin and CD1a share a common intracellular pathway in LCs, traveling through identical intracellular compartments (Salamero et al, 2001;Mc Dermott et al, 2002). Hunger et al (2004) have reported that nonpeptide antigens of Mycobacterium leprae are presented by freshly isolated epidermal LCs to T cell clones derived from the cells of leprosy patients, in a CD1a-restricted Langerin-dependent manner. BGs may therefore correspond to a specialized membrane domain of the ERC, devoted to the loading of CD1a with glycolipids internalized and routed to the BGs by Langerin, as suggested previously by Mc Dermott et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Langerin and CD1a share a common intracellular pathway in LCs, traveling through identical intracellular compartments (Salamero et al, 2001;Mc Dermott et al, 2002). Hunger et al (2004) have reported that nonpeptide antigens of Mycobacterium leprae are presented by freshly isolated epidermal LCs to T cell clones derived from the cells of leprosy patients, in a CD1a-restricted Langerin-dependent manner. BGs may therefore correspond to a specialized membrane domain of the ERC, devoted to the loading of CD1a with glycolipids internalized and routed to the BGs by Langerin, as suggested previously by Mc Dermott et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…PIM and LAM may represent special cases in which a single lipid can activate T cells indirectly through TLRs and also directly through TCRs. However, further studies of LAM will be needed to determine whether the dominant mechanism of T activation involves synthesis of new CD1 proteins or presentation of LAM bound within the CD1b groove (4,18). These in vitro studies of human monocytes now suggest that the simultaneous delivery of both types of activating signals by intact bacteria or sloughed lipids could promote the efficient uptake and presentation of foreign lipids by those myeloid precursors of DCs that encounter pathogens at sites of infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, myeloid dendritic cells use the mannose receptor (CD206) and Langerhans cells use langerin (CD207) to deliver exogenous lipid Ags to endosomes (17,18), where saposin lipidtransfer proteins and a low pH environment promote binding of lipid Ags to CD1 proteins (19 -22). Such endosomal loading pathways are necessary for efficient T cell activation by most or all known bacterial lipid Ags, including mycolic acid, lipoarabinomannan (LAM), glucose monomycolate (GMM), mannosyl phosphomycoketides, and didehydroxymycobactins (DDM) (1,4,(23)(24)(25).…”
mentioning
confidence: 99%
“…Lectin-binding receptors including the mannose receptor are required for efficient endocytosis of glycoprotein (33) and glycolipid (34,35) Ags for their presentation to T cells. In the present study, it was not possible to differentiate whether the carbohydrate moiety was required for efficient Ag uptake/processing or if it was directly involved in T cell recognition.…”
Section: Discussionmentioning
confidence: 99%